Walking strategies in subjects with congenital or early onset strabismus - Aprile, Irene; Ferrarin, Maurizio; Padua, Luca; Di Sipio, Enrica; Simbolotti, Chiara; Petroni, Sergio; Tredici, Costanza; Dickmann, Anna (Frontiers in Human Neuroscience, 2014)
Introduction. In congenital strabismus, sensory adaptations occur hampering the correct development of normal binocular vision. The aim of this study is to investigate if patients with congenital or early onset exotropic or esotropic strabismus adopt different walking strategies with respect to healthy subjects. Our hypothesis is that the abnormal binocular cooperation, occurring in patients with exotropic or esotropic strabismus, could influence neurosensorial adaptation of the gait pattern. Materials and Methods. Twenty-five patients were enrolled:19 with esotropic (ESO) and 6 with exotropic strabismus (EXO). All patients underwent a ophthalmological and orthoptic evaluation. Biomechanical data were collected using a stereophotogrammetric system and a force platform. Twenty-seven age-matched healthy subjects (HS) were used as controls. Results. The comparison between patients with ESO and patients with EXO strabismus showed that the maximal power at the knee and at the ankle was lower in EXO group (p<0.01 and p<0.05 respectively). The step width was statistically different between ESO and EXO groups (p<0.01), lower in patients with ESO and higher in patients with EXO strabismus when compared with HS (though not statistically significant). The deviation angle values showed a relationship with the step width (at the near fixation p<0.05) and with the maximal power at the knee and at the ankle (at the far fixation for the knee p<0.001 and for the ankle p<0.05; at the near fixation for the knee p<0.05): in the patients with EXO the increased angle deviation is related to larger step width and to lower power at the knee and at the ankle. In the patients with ESO strabismus this relationship is less robust. Discussion. Patients with EXO and ESO strabismus adopt different strategies to compensate their walking difficulties, and these strategies are likely due to an expanded visual field in patients with EXO and to a reduced visual field in patients with ESO strabismus.